Diversity and Inclusion of Women working as Engineers: A comparative study between Kosovo and Ireland. Issue 13 (2021) - Bula, Ines; Kent, Mary Doyle; Bula, Edin; Hajrizi, Edmond
Abstract: The primary focus of this paper is to investigate the diversity and inclusion of women working as engineers in Kosovo. A comparison is made with Ireland. It focuses on the lack of support from the employer, society itself and family. Paper is divided in two continuous paper. In this second paper, lack of governmental supports for maternity leave and childcare are investigated. The qualitative approach used in this research will focus on interviews with women working in Kosovo and Ireland and will ask questions about their perceived socio-economic difficulties, flexibility issues and lack of opportunity for career advancement. Through this detailed analysis a clear picture will emerge of the challenges of Kosovar women in their workplaces in the field of engineering. Also, as there is such a small number of women in the field of engineering, we ask the question is there a significant amount of human potential being unused, misused or underuse? How does the division of professions, based on traditional gender roles, lose out on human, institutional and global values?